Control de bienes y equipos del Departamento de Bodega del Cuerpo de Bomberos de Babahoyo - Andrade Macias, Roberto Carlos (2021)
This study is oriented to the control of goods and equipment of the fire department of the city of Babahoyo. The inquiry made is related to the line of investigation that is designated as Financial Administration and Social Commitment, for which the legal bases applicable to this case analysis are taken as references; in the same way, its main objective will be to decide if the regulations imposed by law are fully complied with. The method for obtaining information was an interview in which it was found that the body is a firefighter does not use a type of tool to control its goods and equipment, therefore the objective of this case study is that the warehouse manager and the administrator keep a control of the goods and equipment in an adequate way respecting the order of entry and exit of the products. The performance, control and proper use of long-term administrative assets, in the public area, has been a problem over time that is triggered by the poor organization of its resources, despite the reality of laws, regulations, rules and agreements that regulate the stays of said in the institutions belonging to the state. It is taken into account that in all administrative units the respective physical verification of the assets will have to be made, at least once, every fiscal year, in order to decide the life of the assets that they will be able to be, depending on the time. and of properties that the law establishes, scrapped, disposed of, reused, exterminated, discharged or in any case donated.